2009
DOI: 10.1111/j.1540-5893.2009.00390.x
|View full text |Cite
|
Sign up to set email alerts
|

Expertise, Experience, and Ideology on Specialized Courts: The Case of the Court of Appeals for the Federal Circuit

Abstract: What roles do prior expertise and accumulated experience play in shaping ideologically consistent voting on a specialized court? Using a dataset of obviousness patent cases from the Court of Appeals for the Federal Circuit spanning 1997–2007, we show that prior expertise enhances the influence of ideology on judicial decisionmaking, but that accumulated experience does not. In addition, we build on previous work and show that ideology is a factor in decisionmaking in technical areas of law, contrary to the rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 66 publications
2
33
0
Order By: Relevance
“…More specifically, we think that expertise may act to accentuate the use of ideology in the decision‐making process—hence the fact that the interaction between ideology and expertise is significant and in the expected direction. Though we have detailed this process elsewhere (Miller and Curry 2009), it is worth repeating here that the relationship between expertise and ideological decision making is best understood in terms of motivation. In complex areas of law, such as patent law, we believe that ideological decision making is normally difficult or unattractive for nonexperts because they lack the underlying motivation to view legally or factually complex cases within an ideological framework.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More specifically, we think that expertise may act to accentuate the use of ideology in the decision‐making process—hence the fact that the interaction between ideology and expertise is significant and in the expected direction. Though we have detailed this process elsewhere (Miller and Curry 2009), it is worth repeating here that the relationship between expertise and ideological decision making is best understood in terms of motivation. In complex areas of law, such as patent law, we believe that ideological decision making is normally difficult or unattractive for nonexperts because they lack the underlying motivation to view legally or factually complex cases within an ideological framework.…”
Section: Discussionmentioning
confidence: 99%
“…Jacoby et al. (1986) suggest that expertise is often incorrectly conflated with experience, and Miller and Curry (2009) have demonstrated the validity of this conclusion with respect to the adjudication of patent cases in particular. Specifically, their study indicated that prior expertise represented a significant determinant of judicial decision making in that legal area, but accumulated experience did not.…”
Section: The Federal Circuit Patents and The Law Of Obviousnessmentioning
confidence: 99%
See 1 more Smart Citation
“…Bearing in mind scholarship, discussed below, that concludes that judges also utilize these two modes of information processing (Guthrie, Rachlinski, and Wistrich ), this assessment becomes even more sensible if one conceives of specialization's influence on judicial decision making as primarily related to motivation. As has been generally noted elsewhere (e.g., Miller and Curry ; Miller and Curry ; Krosnick ; McGraw and Pinney ), specialists tend to be better able and more highly motivated to process information systematically than nonspecialists. “Increases in level[s] of motivation are associated with a greater likelihood of systematic [System 2] processing” (Chen, Duckworth, and Chaiken , 47), and, as noted above, scholars have found the utilization of such processing to be affiliated with ideologically motivated reasoning.…”
Section: The Landscape Of Judicial Specializationmentioning
confidence: 68%
“…In order to establish a theoretical foundation for our expectation that specialists will be more ideological in their decision making than their nonspecialist counterparts and to highlight potential mechanisms by which specialists may influence their nonspecialist colleagues, we turn to the emerging literature on the effects of specialization and expertise in judicial decision making. Although ideology's influence on judicial decision making is well established in many contexts (Hettinger, Lindquist, and Martinek ; Segal and Spaeth ; Goldman ; Goldman ), relatively few studies have investigated its relationship to judicial choice in conjunction with specialization in particular subject matters (Miller and Curry ; Unah ; Hansen, Johnson, and Unah ; see Baum ). To the extent that such forays have been made, they have centered on the idea that specialization may be especially relevant to ideology's influence within difficult or technical areas of law.…”
Section: The Landscape Of Judicial Specializationmentioning
confidence: 99%